‘A good decision is the one that feels right for me’: codesign with patients to inform theoretical underpinning of a decision aid website - Kohut, K; Morton, K; Hurley, K; Turner, L; Dale, C; Eastbrook, S; Gold, R; Henwood, K; Patton, S; Punjabi, R; White, H; Young, C; et al. (Wiley, 2023)
Introduction: Patient decision aids (PtDA) complement shared decision-making with healthcare professionals and improve decision quality. However, PtDA often lack theoretical underpinning. We are codesigning a PtDA to help people with increased genetic cancer risks manage choices. The aim of an innovative workshop described here was to engage with the people who will use the PtDA regarding the theoretical underpinning and logic model outlining our hypothesis of how the PtDA would lead to more informed decision-making.